Obstructive sleep apnea syndrome as a cause of resistant hypertension - Parati, Gianfranco; Ochoa, Juan Eugenio; Bilo, Grzegorz; Mattaliano, Paola; Salvi, Paolo; Kario, Kazuomi; Lombardi, Carolina (Hypertension research, 2014)
Evidence has consistently supported the association of obstructive sleep apnea syndrome (OSAS) with an increased prevalence of hypertension. It has also been shown that the severity of OSAS is directly correlated with the degree of blood pressure (BP) elevation and that hypertension occurring in subjects with OSAS is more likely to be severe, resistant to antihypertensive treatment and associated with alterations in day-to-night BP changes. Proposed mechanisms for the pathogenesis of OSAS-related hypertension include the activation of the sympathetic nervous system, alterations in autonomic cardiovascular (CV) modulation, the activation of the renin-angiotensin-aldosterone system, endothelial dysfunction, systemic and vascular inflammation, oxidative stress, metabolic abnormalities, arterial stiffness and alterations in cardiac function and structure. Given the adverse prognostic implications of OSAS-related hypertension for CV morbidity and mortality, the confirmation of resistant hypertension by using ambulatory BP monitoring (ABPM) and the identification of alterations in day-to-night BP changes is of the utmost importance to implement more aggressive strategies for achieving BP control. In turn, the proper identification and implementation of specific treatment strategies for OSAS (that is, continuous positive airway pressure) in subjects with resistant hypertension may promote BP control and optimize CV protection. The present paper will review the evidence supporting the association of OSAS with resistant hypertension and the proposed mechanisms for this association. It will also address the role of ABPM in the confirmation of resistant hypertension in subjects with OSAS and whether the proper identification and management of OSAS in subjects with resistant hypertension will improve BP control.